PENGARUH PERMAINAN TRADISIONAL BAKIAK TERHADAP KETERAMPILAN SOSIAL SISWA KELAS V DI SD NEGERI 54 SINGKAWANG TAHUN AJARAN 2024 - Shohifah Aulia; Wasis Suprapto; Dina Anika Marhayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to: 1) To determine the difference in social skills between students who are given traditional clog games and classes that are not given traditional clog games; 2) To find out how much influence the traditional game of Bakiak has on improving the social skills of fifth grade students at SD Negeri 54 Singkawang; 3) To find out how students respond to traditional clog games in class V at SD Negeri 54 Singkawang. This research was conducted at SD Negeri 54 Singkawang. This type of research is quantitative research method True experiment design, in the form of Posttest Only Control Group Design. The population in this study were all fifth grade students of SD Negeri 54 Singkawang in the 2024 school year totaling 55 students, namely 27 VA class students and 28 VB class students. Samples were taken using non-probability sampling techniques. Data collection techniques using non-test techniques in the form of a social skills questionnaire containing 20 statements and a student response questionnaire to the traditional clog game containing 20 statements. Data analysis techniques use Normality test, Homogeneity test, hypothesis testing, Effect Size, and calculating responses. The results of the analysis found that the data was normally distributed. The results showed 1) there were differences in social skills between students who were given traditional clog games and classes that were not given traditional clog games. After being calculated with a two-sample t test, the tcount> ttable is 4.8875> 2.0057, so Ha is accepted and Ho is rejected. 2) The traditional clog game has a big effect with a high category on the social skills of fifth grade students of SD Negeri 54 Singkawang in the experimental class who received treatment with the effect size test results of 1.365147. 3) The average student response to the traditional clog game was obtained at 87% with a very high category range, So it can be concluded that there is an effect of traditional clog games on the social skills of fifth grade students at SD Negeri 54 Singkawang.